Pengaruh Media Papan Pintar Terhadap Hasil Belajar Siswa Kelas II Mis Mutiara Sei Mencirim - Muhammad Yasir; Fibri Rakhmawati; Rora Rizky Wandini (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2023)
Media plays an important role in the learning process because it can help achieve learning objectives. The purpose of this study was to see how the effect of using smart board media on students' addition and subtraction learning outcomes. This study used a quantitative method with a quasi-experimental research design. The population in the study was entirely class II students totalling 29 students, with a sample of 14 students of class II-A as the experimental class and 15 students of class II-B as the control class. Total sampling was used for sampling. To analyse the data, the Wilcoxon test was used which was carried out with SPSS version 20. The results showed that the use of smart boards had an effect on student learning outcomes in addition and subtraction material, namely the use of smart board media increased student learning outcomes when compared to conventional models. The use of smart board media in particular improves student learning outcomes with an average achievement of 83.2 very good compared to the conventional model which reaches an average of 63.3 with a moderate category. This research can be used to determine the effect of smart board media using other variables.